For the function \( f \), given below, find the antiderivative \( F \) that satisfies \( F(1)=1 \). \( f(x)=x^{6}-3 x^{-4}+5 \) The antiderivative that satisfies the given condition is \( F(x)=\square \).
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To find the antiderivative \( F(x) \) of the function \( f(x) = x^{6} - 3x^{-4} + 5 \), we can integrate term by term: \[ F(x) = \int f(x) \, dx = \int (x^{6} - 3x^{-4} + 5) \, dx \] Calculating this, we have: \[ F(x) = \frac{x^{7}}{7} + 3x^{-3} + 5x + C \] Now, we need to determine the constant \( C \) to satisfy the condition \( F(1) = 1 \): \[ F(1) = \frac{1^{7}}{7} + 3(1^{-3}) + 5(1) + C = \frac{1}{7} + 3 + 5 + C \] This simplifies to: \[ F(1) = \frac{1}{7} + 8 + C = \frac{1}{7} + \frac{56}{7} + C = \frac{57}{7} + C \] Setting this equal to 1: \[ \frac{57}{7} + C = 1 \] To isolate \( C \): \[ C = 1 - \frac{57}{7} = \frac{7}{7} - \frac{57}{7} = -\frac{50}{7} \] Thus, substituting \( C \) back into \( F(x) \): \[ F(x) = \frac{x^{7}}{7} + 3x^{-3} + 5x - \frac{50}{7} \] So the antiderivative that satisfies the given condition is: \[ F(x) = \frac{x^{7}}{7} + 3x^{-3} + 5x - \frac{50}{7}. \]